Human Resource Management Practices and Turnover Intention: the Mediating Role of Perceived Organizational Support in Tertiary Institutions in Nigeria - Dung Paul, Gadi; Kee Mui Hung, Daisy (International Journal of Engineering and Technology, 2018)
Globally, each institution is now challenged with key problems arising out of globalization, anxiety for profitability, and fast technological advancements tied to the emergence of the new intellectual capital. However top managers are concerned with the problem of maintaining and retaining creative and innovative workers to stay.Â The current study is to establish the influence of human resource management (HRM) practices (Training and Development, Recruitment and Selection, Compensation and Performance appraisal) and mediating effect of perceived organizational support on employee turnover intention. The samples of 254 employees from 10 Tertiary Institutions of Plateau State were selected using convenient sampling. SPSS.20 version was used to analyze the data collected. This study found that all human resource practices in this study have a positive and significant impact on employee retention.Â Â Management and top managers of the establishment, pursuing to reduce the level of employee turnover, the end results are articulate: increase in HMR practices can meaningfully improve job satisfaction and assisting to reduce intention to quit. In the underlying context of â€˜â€™creative and innovative talent warâ€™â€™ organizations that are the most proactive in the enactment of HRM practices, that is, the methods designed to improve the skills of employees, to inspire them to use these abilities and encourage them in their decision making at work, will be the managers that possible to retain competent employees.